ALTAA: Analysis of long-term activity patterns in ant colonies - Oh, Jinook; Cremer, Sylvia (Methods in Ecology and Evolution)
1. Collective behaviours are a fascinating study area due to the emergent properties that can only arise in groups of interacting individuals. However, their quantitative study is often impaired by technical difficulties, creating either low-quality and sparse data or impractical data amounts, particularly when capturing large groups over long periods of time. Common challenges arise from recording group members with as little obscuring of each other as possible, as well as in generating manageable data amounts with as high as possible information content. 2. We here provide a multicomponent system that allows to record, analyse and simulate the long-term spatiotemporal activity patterns of insect collectives, especially ant colonies. Our Ant Observing System, ALTAA, comprises a flat-nest design to prevent occlusion of individuals, a recording system running on a low-power single-board-computer, and a set of computer programmes performing quantitative analyses to guide the formation and validation of rules underlying the observed collective patterns. Our system is scalable in that it allows parallel, continuous observation of a high number of colonies using low memory space, with colony maintenance requirements (e.g. feeding, nest humidity) being achieved at lowest possible disturbance by the experimenter. 3. We showcase the potential of the system in a study using the black garden ant, Lasius niger, where we analyse the spatiotemporal effects of different group sizes (1, 6, 10 ants), brood (larvae) presence or absence, as well as of different nest geometries, over a period of 1 week. We show that the ants' motion activity has a weak periodicity in the range of 20 to 120 min promoted by larval presence, and that ants are spatially attracted to their larvae, the water source and the walls. We also find that the presence of nestmates lowers an individual ant's motion activity. Observed data are compared to simulations of the temporal activity of the ants. 4. ALTAA provides a powerful toolkit to quantify and interpret spatial and temporal collective activity patterns in (social) insects over extended periods.

Antiviral immune response reveals host-specific virus infections in natural ant populations - Viljakainen, Lumi; Fürst, Matthias; Grasse, Anna V; Jurvansuu, Jaana; Oh, Jinook; Tolonen, Lassi; Eder, Thomas; Rattei, Thomas; Cremer, Sylvia (Frontiers in Microbiology)
Hosts can carry many viruses in their bodies, but not all of them cause disease. We studied ants as a social host to determine both their overall viral repertoire and the subset of actively infecting viruses across natural populations of three subfamilies: the Argentine ant (Linepithema humile, Dolichoderinae), the invasive garden ant (Lasius neglectus, Formicinae) and the red ant (Myrmica rubra, Myrmicinae). We used a dual sequencing strategy to reconstruct complete virus genomes by RNA-seq and to simultaneously determine the small interfering RNAs (siRNAs) by small RNA sequencing (sRNA-seq), which constitute the host antiviral RNAi immune response. This approach led to the discovery of 41 novel viruses in ants and revealed a host ant-specific RNAi response (21 vs. 22 nt siRNAs) in the different ant species. The efficiency of the RNAi response (sRNA/RNA read count ratio) depended on the virus and the respective ant species, but not its population. Overall, we found the highest virus abundance and diversity per population in Li. humile, followed by La. neglectus and M. rubra. Argentine ants also shared a high proportion of viruses between populations, whilst overlap was nearly absent in M. rubra. Only one of the 59 viruses was found to infect two of the ant species as hosts, revealing high host-specificity in active infections. In contrast, six viruses actively infected one ant species, but were found as contaminants only in the others. Disentangling spillover of disease-causing infection from non-infecting contamination across species is providing relevant information for disease ecology and ecosystem management.

A comparison between common marmosets (Callithrix jacchus) and human infants sheds light on traits proposed to be at the root of human octave equivalence - Wagner, Bernhard; Šlipogor, Vedrana; Oh, Jinook; Varga, Marion; Hoeschele, Marisa (Developmental Science)
Two notes separated by a doubling in frequency sound similar to humans. This “octave equivalence” is critical to perception and production of music and speech and occurs early in human development. Because it also occurs cross-culturally, a biological basis of octave equivalence has been hypothesized. Members of our team previousy suggested four human traits are at the root of this phenomenon: (1) vocal learning, (2) clear octave information in vocal harmonics, (3) differing vocal ranges, and (4) vocalizing together. Using cross-species studies, we can test how relevant these respective traits are, while controlling for enculturation effects and addressing questions of phylogeny. Common marmosets possess forms of three of the four traits, lacking differing vocal ranges. We tested 11 common marmosets by adapting an established head-turning paradigm, creating a parallel test to an important infant study. Unlike human infants, marmosets responded similarly to tones shifted by an octave or other intervals. Because previous studies with the same head-turning paradigm produced differential results to discernable acoustic stimuli in common marmosets, our results suggest that marmosets do not perceive octave equivalence. Our work suggests differing vocal ranges between adults and children and men and women and the way they are used in singing together may be critical to the development of octave equivalence.

Naïve poison frog tadpoles use bi-modal cues to avoid insect predators but not heterospecific predatory tadpoles - Szabo, B; Mangione, R; Rath, M; Pašukonis, A; Reber, SA; Oh, Jinook; Ringler, M; Ringler, E (Journal of Experimental Biology)
For animals to survive until reproduction, it is crucial that juveniles successfully detect potential predators and respond with appropriate behavior. The recognition of cues originating from predators can be innate or learned. Cues of various modalities might be used alone or in multi-modal combinations to detect and distinguish predators but studies investigating multi-modal integration in predator avoidance are scarce. Here, we used wild, naive tadpoles of the Neotropical poison frog Allobates femoralis ( Boulenger, 1884) to test their reaction to cues with two modalities from two different sympatrically occurring potential predators: heterospecific predatory Dendrobates tinctorius tadpoles and dragonfly larvae. We presented A. femoralis tadpoles with olfactory or visual cues, or a combination of the two, and compared their reaction to a water control in a between-individual design. In our trials, A. femoralis tadpoles reacted to multi-modal stimuli (a combination of visual and chemical information) originating from dragonfly larvae with avoidance but showed no reaction to uni-modal cues or cues from heterospecific tadpoles. In addition, visual cues from conspecifics increased swimming activity while cues from predators had no effect on tadpole activity. Our results show that A. femoralis tadpoles can innately recognize some predators and probably need both visual and chemical information to effectively avoid them. This is the first study looking at anti-predator behavior in poison frog tadpoles. We discuss how parental care might influence the expression of predator avoidance responses in tadpoles.

Early life differences in behavioral predispositions in two Alligatoridae species - Reber, Stephan A.; Oh, Jinook; Janisch, Judith; Stevenson, Colin; Foggett, Shaun; Wilkinson, Anna (Animal Cognition)
Behavioral predispositions are innate tendencies of animals to behave in a given way without the input of learning. They increase survival chances and, due to environmental and ecological challenges, may vary substantially even between closely related taxa. These differences are likely to be especially pronounced in long-lived species like crocodilians. This order is particularly relevant for comparative cognition due to its phylogenetic proximity to birds. Here we compared early life behavioral predispositions in two Alligatoridae species. We exposed American alligator and spectacled caiman hatchlings to three different novel situations: a novel object, a novel environment that was open and a novel environment with a shelter. This was then repeated a week later. During exposure to the novel environments, alligators moved around more and explored a larger range of the arena than the caimans. When exposed to the novel object, the alligators reduced the mean distance to the novel object in the second phase, while the caimans further increased it, indicating diametrically opposite ontogenetic development in behavioral predispositions. Although all crocodilian hatchlings face comparable challenges, e.g., high predation pressure, the effectiveness of parental protection might explain the observed pattern. American alligators are apex predators capable of protecting their offspring against most dangers, whereas adult spectacled caimans are frequently predated themselves. Their distancing behavior might be related to increased predator avoidance and also explain the success of invasive spectacled caimans in the natural habitats of other crocodilians.